Economic basis and practicalities of washland creation on the somerset levels and moors - Morris, J.; Vivash, R. M.; Alsop, D.; Lawson, C. S.; Leeds-Harrison, P. B.; Bailey, A. P. (Cranfield University, 2002)
In Somerset, the Wise use of Floodplains (WUF) Project has developed new ways of helping stakeholders in the River Parrett Catchment to find sustainable solutions for the management of water, both in flood events and throughout the year.